From script to space: Integrating Nüshu heritage into interior design narratives - Yu Qin Lim; Azizi Bahauddin (ARTEKS : Jurnal Teknik Arsitektur)
Nüshu, or “women’s script”, is a unique calligraphy and female culture traditionally inherited among women in Jiangyong County, Hunan Province, China. Regarded as “the secret language of women”, it has recently been revitalised. Besides the museum dedicated to preserving Nüshu, previous studies have explored its characteristics, linguistic and literacy aspects, cultural significance, and applications in digital technology. Despite its integration into product, fashion, and multimedia designs, widespread awareness remains scarce. This research aims to integrate Nüshu heritage into feminine interior design to honour past women’s wisdom, courage, and creativity with two objectives: to identify significant Nüshu elements for integration into feminine spaces and to develop design approaches for this integration to enhance cultural narrative and depth in feminine interior spaces. This study adopted a qualitative approach where a female interior designer and a female architect in Malaysia were interviewed to gain insights into feminine space designs. Content analysis was also conducted on an exhibition design with feminine attributes, as an example of narrative in feminine spaces. Guided by feminist theory, the discussion centred on infusing feminine interiors with Nüshu cultural symbolisms. Therefore, this paper underscores the significance of incorporating Nüshu elements into feminine interiors to enhance cultural appreciation and connection.